Comparative Decalcification Methods, Radiocarbon Dates, and Stable Isotopes of the VIRI Bones - Tuross, Noreen (Radiocarbon, 2012)
The Fifth International Radiocarbon Comparison (VIRI) provided a suite of 5 bone samples with consensus ages ranging from 969 to 39,305 14C yr BP (Scott et al. 2010). These bones were used herein in a comparison of decalcification methods using either HCl or EDTA to produce collagen, and the results demonstrate age concordance between both preparation methods and the VIRI consensus values. Additional isotopic analyses of the collagen (13C, 15N, and 18O) illustrate the increasing sensitivity of carbon, nitrogen, and oxygen isotopes in assessing gelatin degradation.